Incidence and determinants of mortality among patients with colorectal cancer in oncology centers of Amhara region, Ethiopia, 2024: multicenter retrospective follow up study - Getachew Tesfaw Walle; Tegene Atamenta Kitaw; Seteamlak Adane (BMC Cancer)
Abstract Introduction Colorectal cancer is a significant cause of mortality globally, with several factors impacting patient outcomes, including access to healthcare, early detection, and treatment. Despite this, the specific factors affecting incidence of death among colorectal cancer patients in the Amhara region have not been thoroughly investigated. Thus, this study seeks to assess incidence and determinants of mortality among colorectal cancer patients in Amhara Region oncology centers. Results The mean age of the participants was 48.6 years (SD ± 15). Median survival time was 23.8 months. The overall incidence rate or incidence density of a colorectal cancer mortality rate was 2.9 per 100 person-months (95% CI: 2.5–3.4). Survival rates of colorectal cancer patients 1and 5 year was 69.78% and 16.1%, respectively. The result of the multivariable analysis showed that colorectal cancer patients who had presenting symptoms [AHR = 2.67 (95% CI: 1.95, 3.67)], Base line HGB level < 12.5 mg/dl [AHR = 1.63 (95% CI: 1.12, 2.37)], WHO or ECOG poor performance status [AHR = 2.99 (95% CI: 2.17, 4.12), late stage of cancer [AHR = 2.32 (95% CI: 1.42, 3.79)] and location of tumor on colorectal [AHR = 1.76 (95% CI: 1.20, 2.55)] were significantly associated with mortality of colorectal cancer. Conclusion and recommendation The study highlights significant findings on the survival and mortality of colorectal cancer patients. The overall mortality rate was 2.9 per 100 person-months. Multivariable analysis identified presenting symptoms, low baseline hemoglobin levels, poor performance status, late-stage cancer, and tumor location as significant predictors of mortality. Highlighting the need for early detection and targeted care strategies.